Teacher and Peer Responses to Warning Behavior in 11 School Shooting Cases in Germany - Fiedler, Nora; Sommer, Friederike; Leuschner, Vincenz; Ahlig, Nadine; Göbel, Kristin; Scheithauer, Herbert (Frontiers in Psychology, 2020)
Warning behaviour prior to an act of severe targeted school violence was often not recognized by peers and school staff. With regard to preventive efforts, we attempted to identify barriers to information exchange in German schools, and understand mechanisms that influenced the recognition, evaluation, and reporting of warning behaviour through a teacher or peer. Our analysis is based on inquiry files from eleven cases of German school shootings that were obtained during the three-year research project “Incident and case analysis of highly expressive targeted violence (TARGET)". We conducted a qualitative retrospective case study to analyze witness reports from school staff and peers. Our results point to subjective explanations used by teachers and peers towards conspicuous behaviour (e.g., situational framing, typical adolescent behaviour), as well as reassuring factors that indicated harmlessness (e.g., no access to a weapon). Additionally, we found organizational barriers similar to those described in US-American case studies (e.g., organizational deviance).